Percepción de las circunstancias que generan conductas suicidas en los wayuu (2023)
The present investigation describes the perception of the circumstances that generate suicidal behaviors in members of the Wayuu community of Cerro of the Teta in the municipality of Uribía - La Guajira. This study corresponds to a qualitative research, with a descriptive scope, in addition, it has a narrative design, with a descriptive scope and its paradigm is social constructivist. Regarding the study population, it corresponds to 73 people while the selected sample is 4 members of the aforementioned community: 1 piache, 1 adolescent, 1 adult and 1 older adult, to whom an in-depth interview was used with some questions. previously established based on the research topic and according to 4 organized categories: sociodemographic characterization, family aspects, ways of coping with suicide and level of perception of suicidal behavior, which allowed us to understand the reality of the worldview of this culture on the subject of suicide. subject of study, in which their point of view is that suicide is reprehensible and unacceptable, it is a situation that is not well regarded and that generates shame in the community.